Risk of Mental Disorders in Children and Adolescents With Atopic Dermatitis: A Systematic Review and Meta-Analysis - Xie, Qian-Wen; Dai, Xiaolu; Tang, Xinfeng; Chan, Celia H. Y.; Chan, Cecilia L. W. (Frontiers in Psychology, 2019)
Assessing the psychological effects on children and adolescents of suffering atopic dermatitis (AD) is essential, when planning successful management. This study aimed to systematically review the literature regarding risk of mental disorders in children and adolescents with, or without, AD; and to explore confounders. We identified potentially relevant studies from EMBASE, MEDLINE, PsycINFO, ERIC, the British Nursing Index, the Family and Society Studies Worldwide, the Social Work Abstracts, and the Sociological Abstracts from inception to Sep 30, 2018. Investigators independently screened titles and abstracts, and then full-texts. Investigators independently extracted data from included studies. Meta-analyses using random-effects models were performed, reporting odds ratios (ORs; 95% CIs). Thirty-seven studies (n = 2,068,911 children/ adolescents) were included. Meta-analysis of 35 studies found that children and adolescents with AD had significantly higher risk of total mental disorders than those without AD (OR = 1.652; 95% CI, 1.463–1.864). There was no significant difference in risks for ADHD (OR = 1.563; 95% CI, 1.382–1.769); sleep disorders (OR = 2.100; 95% CI, 1.322–3.336); anxiety (OR = 1.339; 95% CI, 1.062–1.687); depression (OR = 1.402 95% CI, 1.256–1.565); conduct disorder (OR = 1.494 95% CI, 1.230–1.815); or ASD (OR = 2.574; 95% CI, 1.469–4.510; Qb = 8.344, p = 0.138). Race/ethnicity of child, target of comparison, type of studies, representativeness of the sample, measures of AD and mental disorders were significant moderators for total mental disorders. Integrated, holistic, multidisciplinary management of pediatric AD is significantly important, which emphasizes the well-being of the whole person.